PENGARUH INFLASI, PRODUK DOMESTIK BRUTO, CORRUPTION PERCEPTION INDEX, DAN INDEKS HARGA SAHAM TERHADAP FOREIGN DIRECT INVESTMENT DI INDONESIA PERIODE (2005-2014) - AFNI ROMADHONA, NURUL (Jurnal Ilmu Manajemen (JIM), 2016)
The purpose of this study was to investigate and analyze the effect of inflation, gross domestic product, corruption perception index and the stok price index of the Foreign Direct Investment. This Research kuantitatif Research and it used quantitative Research. Variabel in the Research is use secondary data obtained from The offical website Badan Pusat Statistik, Bursa Efek Indonesia, and Transparency International This Study used 9 economy sector in Indonesia as sampel and multiple regresion analysis during 2005-2014. Results from this study is the simultaneous inflation, gross domestic product, corruption perception index, and the stock prices index have an impact on foreign direct Investment. Partially that there is have no significant effect of inflation, gross domestic product, and the stock price index on FDI. But different result with the corruption perception index that have a significant effect on FDI. Keywords: Inflation, Gross Domestic Product, Corruption Perception Index, Stock Price Index, and Foreign Direct Investment.